Social Justice Design and Implementation in Library and Information Science - Paul, Snehasish (Journal of Data Science, Informetrics, and Citation Studies)
In recent years, the Library and Information Science (LIS) profession has reached a significant crossroads, as it must address long-standing systemic inequities while remaining responsive to shifting community needs. Social Justice Design and Implementation in Library and Information Science, edited by Bharat Mehra, is a compelling and timely response to the challenge. The Routledge book was published in 2022. The book comprises 18 diverse yet compelling chapters that explore the methods by which social justice can be effectively introduced in the practice, research, education, and policy-making of LIS. More than a conceptual treatise, the book presents social justice as an explicit and strategic process of design, encouraging professionals in LIS to adopt justice-driven outcomes in their everyday, practical work.